Recovery of Post Traumatic Brown?s Syndrome - , Muhammad Khalil Rana, Muhammad Khalil, Tayyaba Gul Malik, Mian Muhammad Shafique, Muhammad Moin (Pakistan Journal of Ophthalmology, 2007)
Brown’s syndrome1, 2, 3 is a motility defect which is characterized by an inability to raise the adducted eye above the horizontal midline, less or no elevation deficit in abducted position. There is slight down shoot of the adducting involved eye with widening of the palpebral fissure on adduction. Exodeviation usually increases as the eyes are moved upward in the midline (V-pattern).